The Influence of the Guided Inquiry Learning Model on Students Ecoliteracy Attitudes on Waste Recycling Materials - Sentosa, Zill Sekar Gading Fawwaz; Marjanah; Setyoko (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Ecoliteracy is the concept of a comprehensive understanding of ecosystems and their environment. The low ecological intelligence or ecoliteracy of students is the background of this study. This study aims to test whether the guided inquiry learning model affects students' ecoliteracy attitudes and how students' ecoliteracy attitudes through guided inquiry learning models on waste recycling materials. The research method used is an experiment with a quantitative approach. The population in this study was the entire class X MIPA SMA Negeri 1 Stabat, which amounted to 216 students. The sample used was random sampling, namely class X MIPA-1 students as an experimental class and class X MIPA-3 as a control class with 72 students. The research only focuses on attitudinal aspects of ecoliteracy competence. Research data were collected through the distribution of questionnaire sheets and observations. The results showed that the average ecoliteracy attitude of students taught using the guided inquiry learning model reached 87.2% in the good category. Meanwhile, the average ecoliteracy attitude of students taught with conventional learning models is 62.7% with sufficient categories. Hypothesis testing is done manually. Experimental class students have a higher percentage of ecoliteracy than control class students. Guided inquiry learning in waste recycling materials is more efficiently used to determine the improvement of students' ecoliteracy attitudes.